Unique Epigenetic Features of Ribosomal RNA Genes (rDNA) in Early Diverging Plants (Bryophytes) - Matyášek, Roman; Krumpolcová, Alice; Lunerová, Jana; Mikulášková, Eva; Rosselló, Josep A.; Kovařík, Aleš (Frontiers in Plant Science, 2019)
Introduction: In plants the multicopy genes encoding ribosomal RNA (rDNA) typically exhibit heterochromatic features and high level of DNA methylation. Here, we explored rDNA methylation in early diverging land plants from Bryophyta (15 species, 14 families) and Marchantiophyta (4 species, 4 families). DNA methylation was investigated by methylation-sensitive Southern blot hybridization in all species. We also carried out whole genomic bisulfite sequencing in Polytrichum formosum (Polytrichaceae) and Dicranum scoparium (Dicranaceae) and used available model plant methyloms (Physcomitrella patents and Marchantia polymorpha) to determine rDNA unit-wide methylation patterns. Chromatin structure was analyzed using in situ hybridization (FISH) and immunoprecipitation (CHIP) assays. Results: In contrast to seed plants, bryophytes rDNAs were efficiently digested with methylation-sensitive enzymes indicating no or low levels of CG and CHG methylation in these loci. The rDNA methylom analyses revealed variation between species ranging from negligible (<3%, P. formosum, P. patens) to moderate (7 and 17% in M. polymorpha and D. scoparium, respectively) methylation levels. There were no differences between coding and non-coding parts of rDNA units and between gametophyte and sporophyte tissues. However, major satellite repeat and transposable elements were heavily methylated in P. formosum and D. scoparium. In P. formosum rDNA, the euchromatic H3K4m3 and heterochromatic H3K9m2 histone marks were nearly balanced contrasting the angiosperms data where H3K9m2 typically dominates rDNA chromatin. In moss interphase nuclei, rDNA was localized at the nucleolar periphery and its condensation level was high. Conclusions: Unlike to seed plants, the rRNA genes seem to escape global methylation machinery in bryophytes. Distinct epigenetic features may be related to rDNA expression and the physiology of these early diverging plants which exist in haploid state for most of their life cycles.